Implementation and analysis of temperature sensor based on pic and wireless sensor network technology / Hairi Anwar Aminuddin - Aminuddin, Hairi Anwar (2009)
Nowadays, technology for sensing and control is currently in high demand on a broad range of applications. Potential applications ranging from hearth care, transportation, environmental monitoring, energy, industrial monitoring and control, military, home automation and many more are taking the advantages of the wireless sensor network technology. Beside low cost and high efficiency, WSN also offers conveniences to the users. This project presents the performance analysis of Wireless Sensor Network (WSN) used in the high-end applications such as temperature sensor. Recently WSN also focuses on national security applications and consumer applications. This project shall demonstrate the performance of WSN models, which have been developed using PIC. Temperature sensor nodes were deployed in the networks to create sensing phenomena. The results recorded that successful throughput from sensor node, strongly depends on the delay setting. Therefore, the important factors and issues pertaining to the WSN performance will also be determined and describe briefly.